Media Crossroads : Intersections of Space and Identity in Screen Cultures - Wojcik, Pamela Robertson, 1964-; Massood, Paula J., 1965-; Matos, Angel Daniel (Book collections on Project MUSE., 2021)
"Media Crossroads is an anthology that examines space and place in film, television, video games, and other media via critical intersectional lenses and other interpretive strategies. The eighteen essays in this volume draw from and build upon research on gender and space across numerous disciplines and situate such studies in conversation with research on sexuality, race, ethnicity, age, class, ability, and other domains of identity as they relate to space. The contributors not only consider the way screens produce intersections between and among various identities through spectatorship, play, and social media, but they also focus on how representations of space in film and media address matters of oppression, discrimination, privilege, and inequity"--